2016
DOI: 10.3390/catal6030032
|View full text |Cite
|
Sign up to set email alerts
|

Production of Resveratrol by Piceid Deglycosylation Using Cellulase

Abstract: Abstract:Resveratrol is a dietary polyphenolic compound widely used in medicine, food, and cosmetic products. The glycoside form of resveratrol, piceid, is also present in several plant materials but is less bioavailable. In this study, enzymatic transformation of piceid into resveratrol using inexpensive cellulase was investigated. Response surface methodology was used to evaluate the effect of reaction parameters, including reaction temperature, reaction time, enzyme amount and pH. The optimal conditions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…HepG2 cells carrying ARE-luciferase constructs 22 were seeded at a density of 5 × 10 4 cells/well in a six-well plate (SPL Life Sciences Co. Ltd) and cultured in 10% v/v FBS-containing DMEM supplemented with 400 μmol L-1 hygromycin (Sigma-Aldrich, St. Louis, MO, USA). Luciferase activity was then determined as previously described.…”
Section: Measurement Of Are-reporter Gene Transcriptional Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 cells carrying ARE-luciferase constructs 22 were seeded at a density of 5 × 10 4 cells/well in a six-well plate (SPL Life Sciences Co. Ltd) and cultured in 10% v/v FBS-containing DMEM supplemented with 400 μmol L-1 hygromycin (Sigma-Aldrich, St. Louis, MO, USA). Luciferase activity was then determined as previously described.…”
Section: Measurement Of Are-reporter Gene Transcriptional Activitymentioning
confidence: 99%
“…Among all the enzymes tested, cellulase was least efficient in piceid deglycosylation, despite being reported to be effective in converting piceid into resveratrol. 24 Viscozyme ® was hereby tested along with the other enzymes because it is also reported to possess the activity of cellulase in accordance with the manufacturer's analysis and thus was expected to deglycosylate piceid in a similar manner to cellulase. The remarkable resveratrol recovery achieved by using VinoTaste ® Pro may be attributed to its -1,3-glucanase activity, which directly hydrolyzes the -1,3-linkage present in piceid.…”
Section: Enzymatic Conversion Of Pure Piceid To Resveratrolmentioning
confidence: 99%
“…Response surface methodology (RSM) is a collection of mathematical and statistical techniques for designing experiments, building models, evaluating the relative significance of multiple independent variables, and determining the optimal conditions for the desired response [ 27 , 28 , 29 , 30 ]. It is used to evaluate the effects of various parameters and their interactions via a small number of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…cuspidatum root potentially represents an excellent source for production of resveratrol (Wang et al, 2013). However, the bioavailability of polydatin is lower than that of resveratrol (Kuo et al, 2016), and studies have shown that human intestinal cells absorb polydatin with greater difficulty and more slowly than resveratrol (Signorelli and Ghidoni, 2005). Therefore, efficient extraction of polydatin from P .…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, β-glucosidase can transform polydatin into resveratrol by catalyzing the hydrolysis of β-glucosidic linkages. This cellulase-based extraction and conversion technology has been widely used in resveratrol production (Nagendra chari et al, 2013; Kuo et al, 2016; Mai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%